Quantitative analysis of methane and glycolate production from microalgae using undiluted wastewater obtained from chicken-manure biogas digester - Thoranit Moungmoon (2020)
© 2020 Elsevier B.V. Microalgal biomass is often used as a raw material in methane production. Some microalgae possess a complex cell-wall structure which has a low degradability of microorganisms in anaerobic digestion. However, some microalgae produce glycolate, which is excreted outside the cell and can be used to produce methane under anaerobic condition. This research aims to investigate microalgal cultivation using wastewater to reduce nutrients and efficiently create glycolate. Two strains of microalgae (Acutodesmus sp. AARL G023, Chlorella sp. AARL G049) and two microalgal consortia were cultivated at dilutions of 0.5-fold (W50), 0.75-fold (W75) and undiluted wastewater (W100). The results showed that the microalgal consortium with undiluted wastewater (WCW100) consisted of Leptolyngbya sp. (30.4%), Chlorella sp. (16.1%) and Chlamydomonas sp. (52.2%), revealed the highest biomass productivity at 64.38 ± 14.54 mg·L−1·d−1 and the highest glycolate productivity at 5.12 ± 0.48 mmol·L−1·d−1. The cultivation of microalgae effectively reduced ammonium‑nitrogen (NH4+-N) and soluble reactive phosphorus (SRP) levels in the wastewater at 43.5 ± 1.3% and 49.6 ± 6.9%. Furthermore, WCW100 showed the highest biogas productivity at 1.44 ± 0.07 mL·g−1·d−1 and the highest methane content at 58.3 ± 6.0% v/v. This study indicates that there is a definite potential of using undiluted wastewater for microalgal biomass production and glycolate production that can reduce the wastewater volume and be applied as a raw material for methane production.